Europe and the United States in the “Asian” 21st Century: The Political, Economicn and Security Context - Milos Balaban (Central European Journal of International & Security Studies, 2010)
While, at the western end of Eurasia, most European states are taking part in a great experiment; broadening and deepening their political, economic and security integration within the EU, at the eastern end of Eurasia, an experiment of no less importance is underway. China, the world’s most populous great power (a relatively poor, centrally controlled country) is being transformed – in a historically short time – into a politically and economically powerful, mature and respected global actor.